The hadal benthopelagic Calanoida from the Kurile-Kamchatka Trench, North Pacific with the description of a new diaixid genus (Copepoda: Calanoida) - Markhaseva, Elena L.; Renz, Jasmin (Zootaxa, 2025)
The new calanoid copepod genus Mixtodiaixis gen. nov., is based on the female and male of its type species, described herein. The specimens were collected in the vicinity of the seabed in the hadal zone of the Kurile-Kamchatka Trench, Pacific Ocean, at depths below 7000 m. Mixtodiaixis kurambiohadalis sp. nov. is a representative of the family Diaixidae distinguished by the mandible gnathobase supplied by 5 teeth and 4 setae, the maxillule praecoxal arthrite with 7 terminal spines, each of the maxilla basal endites armed with two sclerotized and one worm-like sensory setae, and a maxilliped coxal endite that possesses 2 setae. Along with the new diaixid species and genus, 16 representatives of Arietellidae, Tharybidae, Phaennidae, Scolecitrichidae, Aetideidae, Rostrocalanidae and Ryocalanidae were observed in the samples obtained from the hadal of the Kurile-Kamchatka Trench directly above the bottom. In regard to the members of Arietellidae, Diaixidae, Rostrocalanidae, Ryocalanidae and Tharybidae, this is their first record from such a great depths of the World Ocean.